A cross-sectional study of hypertension in an elderly population (75 years and over) with atrial fibrillation: secondary analysis of data from the Birmingham Atrial Fibrillation in the Aged (BAFTA) randomised controlled trial. - Hurley, V; Ireson, R; Fletcher, K; Lip, G; Hobbs, F; Mant, J (2007)
BACKGROUND: Atrial fibrillation and hypertension are two common conditions in the elderly, associated with significant morbidity and mortality. Little information is available regarding the epidemiology of hypertension in elderly patients with atrial fibrillation. SUBJECTS AND METHODS: A secondary analysis of data from the Birmingham Atrial Fibrillation Treatment of the Aged study, a randomised controlled trial of thrombo-prophylaxis in atrial fibrillation in a primary care population. The study population comprised patients aged 75 and over with electrocardiogram (ECG) confirmed atrial fibrillation. Blood pressure was recorded in the general practice surgery on two occasions using standardised methods. History of hypertension was sought from the medical records and from asking the patient. RESULTS: 3059 subjects had ECG confirmed atrial fibrillation. The prevalence of a history of hypertension in this group was 57.5%. The mean systolic blood pressure was 141 mmHg (standard deviation: 21 mmHg) in men and 144 mmHg (22 mmHg) in women. The mean diastolic blood pressure was 79 mmHg (12 mmHg) in men and 80 mmHg in women (12 mmHg). The mean systolic blood pressure was slightly lower than that of the general population aged 75 and over, but the mean diastolic blood pressure was significantly higher in patients in atrial fibrillation (by 8 mmHg). Among the patients with a diagnosis of hypertension, 86.5% were on blood pressure lowering medications. CONCLUSIONS: Hypertension is more commonly diagnosed in older patients with atrial fibrillation than in the general population. The mean systolic blood pressure is slightly lower, but the mean diastolic blood pressure substantially higher in older patients in atrial fibrillation, compared to the general population.